2007
DOI: 10.1507/endocrj.k06-196
|View full text |Cite
|
Sign up to set email alerts
|

TSH-receptor Antibodies Determined by the First, Second and Third Generation Assays and Thyroid-stimulating Antibody in Pregnant Patients with Graves' Disease

Abstract: Abstract. The measurement of TSH receptor antibody (TRAb) has been recommended to predict the risk of neonatal hyperthyroidism (NH) in pregnant women with Graves' disease (GD). For the first generation TRAb (TRAb1) assay with commercial kit (Brahms, Berlin, Germany; or Cosmic co., Tokyo, Japan) an arbitrary limit of 40 U/l or 50% was suggested to indicate risk when measured late in pregnancy. In order to substitute TRAb1 with the second generation TRAb using porcine TSH receptor (pTRAb2) and human recombinant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 12 publications
0
34
0
Order By: Relevance
“…Therefore, the occurrence of neonatal hyperthyroidism seems to be a matter of concern in pregnancies of severe Graves' patients after radioiodine treatment. However, in most cases, as reported by Tajiri, neonatal hyperthyroidisms do not occur because serum TRAb usually decreases during pregnancy even if the serum level of TRAb is high at the first trimester [10,14]. In this study, among patients with high serum TRAb at the first trimester, serum levels of TRAb of mothers Fig.…”
Section: Comparison Of Patients Who Delivered Infants With Neonatal Hmentioning
confidence: 47%
“…Therefore, the occurrence of neonatal hyperthyroidism seems to be a matter of concern in pregnancies of severe Graves' patients after radioiodine treatment. However, in most cases, as reported by Tajiri, neonatal hyperthyroidisms do not occur because serum TRAb usually decreases during pregnancy even if the serum level of TRAb is high at the first trimester [10,14]. In this study, among patients with high serum TRAb at the first trimester, serum levels of TRAb of mothers Fig.…”
Section: Comparison Of Patients Who Delivered Infants With Neonatal Hmentioning
confidence: 47%
“…Previous studies reported an increased risk if TBII level was over 40 IU/l (normal range, !10 IU/l) (25), or over 40 or 70% (26,27) (normal, !10-15%) in late T3. Today, the TBII first-generation assay has been widely replaced by the second-generation assay, and yet only one short study has investigated the TBII value predictive of neonatal hyperthyroidism using this assay (19). The authors compared TBII values determined by four assays, and tried to establish equivalence between first-and second-generation assays.…”
Section: Discussionmentioning
confidence: 99%
“…Instead of solubilized porcine receptors (14,15), these newer assays use recombinant TSHR coated on a solid-phase surface which provides a markedly improved sensitivity and specificity (16,17,18). To our knowledge, the threshold value indicating a risk for fetal or neonatal autoimmune hyperthyroidism with a second-generation TBII assay has only been investigated in one small study (19).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported that the serum TRAb values usually decreased during pregnancy [3,[15][16][17]. As a possible mechanism of this, Amino et al suggested that Th2-dependent humoral immunity is suppressed in human pregnancy [16].…”
Section: Disclosurementioning
confidence: 99%
“…five times the upper limit of the normal range [1,[20][21][22] or > 10 IU/L [15]. We therefore used 10 IU/L as the cut-off value for TRAb in the present study.…”
Section: Disclosurementioning
confidence: 99%